Genótipos da membrana externa, homA e homB, do Helicobacter pylori em pacientes com gastrite, úlcera péptica e câncer gástrico do nordeste do Brasil - Braga Neto, Manuel Bonfim (2013)
Recently, the Hom family of Helicobacter pylori outer-membrane proteins have been studied as novel virulence markers. Most studies have found that the homB gene is strongly associated with peptic ulcer disease (PUD) and the homA gene with non-ulcer disease. Furthermore, it has been shown that the HomB protein plays a role in the proinflammatory properties and adherence of Helicobacter pylori. However, the clinical association and the function of the hom gene remains unclear. This study aimed to determine the prevalence of homA and homB genes and evaluate the association with gastric disease. We evaluated, prospectively, 183 H. pylori-positive patients (48 with gastric cancer, 71 with PUD and 64 with gastritis) undergoing upper digestive endoscopy or surgery at the Hospital Universitário Walter Cantídio, Federal University of Ceará. DNA was extracted, followed by PCR and electrophoresis for genes ureA, vacA, homA e homB. Of the 183 patients evaluated, 47 were homB-positive (25.7%), 85 were homA-positive (46.4%), 42 positive for both homA e homB (22.9%) e 9 patientes were negative for homA and homB. Samples positive for both homA and homB were excluded from the analysis. There was no association between homA and gastric disease. A significant inverse association between homA and PUD (O.R=0.353; p=0.005) and gastric ulcer (O.R=0.304; p=0.032) was found. The homB genotype was significantly associated with PUD (O.R=2.974; p=0.004). Of the 183 patientes, 71% were vacAs1 and 87.9% were vacAm1, considered more virulent strains. The homB genotype was not associated with the vacAs1m1 genotype (p=0.441).These data suggest that in this population the presence of homB gene may be a good predictor for PUD.